Exploring user perspectives of factors associated with use of teletrauma in rural areas. (June 2022) - Wood, Timothy; Freeman, Shannon; Banner, Davina; Martin-Khan, Melinda; Hanlon, Neil; Flood, Frank
Abstract: Background: Despite the existence of universal health care for Canadians, health inequalities persist and those residing in rural regions experience disparities when accessing appropriate services. To enhance access, a teletrauma program was implemented in a rural northern region in western Canada, connecting rural clinicians to urban emergency physicians and trauma specialists during emergency cases. Objective: To explore reasons why teletrauma is used in rural contexts from the perspectives of service users and stakeholders. Methods: 14 semi-structured interviews were conducted with stakeholders, clinicians (physicians, specialists), management, and researchers. Interpretive description methodology guided the study and analysis, and findings were organized thematically. Results: Teletrauma was used to connect clinicians, manage complex cases when weather or distance delayed transfer, and to enable appropriate and timely treatment locally. Teletrauma was more likely to be activated when clinicians were uncomfortable with clinical management, when relationships were established, and when technology was familiar and easy to use. Conclusions: Teletrauma is more than just the technology that is deployed. The establishment of relationships between teletrauma users was vital to the success of teletrauma. To design effective, integrated, and sustainable services, rural clinicians must remain at the center of teletrauma models.